Governance Reforms, Individualization of Human Resource Management (HRM), and Impact on Workplace Behavior—A Black Box?. (3rd May 2020) - Demmke, Christoph
Abstract : The purpose of this article is to discuss the relationship between destandardization and delegation trends; ethical leadership; perceptions of organizational fairness; and justice and workplace behavior. It is argued that current destandardization, delegation, and individualization trends in the field of HRM place additional burdens on managers. In times of de-bureaucratization, more job autonomy and flatter hierarchies, managers change; shape; direct; and alter employeés lives. On the other hand, research has found that justice perceptions of the leader are strongly related to employee outcomes. Still, there is very little evidence on all these trends. In which HR fields can we observe destandardization and delegation trends? What is individualization of HR and how does this relate to ethics? How much discretionary powers have managers in making HR decisions? What forms of leadership behavior impact on what type of organizational justice perceptions? How professional are managers in carrying out these tasks? Are managers aware about the importance of ethical leadership on different forms of justice perceptions? The article concludes that academic discussions about all of these issues are still very rudimentary. Thus, the purpose of this article is to suggest a new important reform agenda in this field.